Emperor, Empress, and the Divine in San Vitale and the Binyang Central Cave - Shin, Junhyoung (Buddhist Christian studies, 2020)
This essay compares historically unrelated religiopolitical iconographic programs executed in Byzantine Empire and Northern Wei China of the sixth century, and points out the common mechanism, through which these two cultures made use of religious imagery to promote imperial authority. They deployed different religious topoi befitting their respective Orthodox Christian and Buddhist-Confucian statecrafts, but arrived at surprisingly similar visual experiences. The key to the visual tactic employed in both sites, I would argue, lies in the trinity and multiplicity of the divine. The apse of San Vitale in Ravenna, completed in the years 547, suggests a double parallelism between Emperor Justinian and Christ that is further mirrored in the relationship between Christ and God the Father. The Binyang Central Cave in Longmen, completed in 523, implies a parallelism between Emperor Xuanwu's succession to his late father, Emperor Xiaowen, and the successive salvific endeavors of the Buddhas of the Three Ages. The religiopolitical theories of Bishop Eusebius of Caesarea (260-340) and the Pure Land patriarch Tanluan (曇鸞, 476-542) provide significant clues to understand these similarities.